Investigation of turn-on voltage shift in organic ferroelectric transistor with high polarity gate dielectric - Nguyen, Chien A. (2013)
Large positive shifts of turn-on voltage Vto were observed in ferroelectric organic thin film transistor using P(VDF-TrFE) copolymer (57–43 mol%) as gate insulator during OFF to ON state sweeping. The shift of the transfer characteristic up to +25 V is attributed to the accumulation of mobile charge carriers (holes) in pentacene layer even during the device OFF state. The observed phenomena were first discussed on the basis of a negative surface potential created by the dipole field of a polar dielectric and trap states in an organic semiconductor layer. It was however found that these were unable to fully address the observed strong Vto shift due to the presence of large polarization in the P(VDF-TrFE) layer. A mechanism of negative polarization-compensating charges which are injected to the insulator region next to the semiconductor layer was proposed and examined to understand the phenomenon. The turn-on voltage is found to change with different magnitude of positive voltage pulses, and corresponds to different amount of charges injected for compensation. Time measurement of drain current shows a transient decaying behavior when gate bias is switched from positive to negative polarity which confirms the trapping of negative charges in the insulator.